2013
DOI: 10.1371/journal.pone.0059299
|View full text |Cite
|
Sign up to set email alerts
|

Generalization versus Specialization in Pollination Systems: Visitors, Thieves, and Pollinators of Hypoestes aristata (Acanthaceae)

Abstract: Many recent studies have suggested that the majority of animal-pollinated plants have a higher diversity of pollinators than that expected according to their pollination syndrome. This broad generalization, often based on pollination web data, has been challenged by the fact that some floral visitors recorded in pollination webs are ineffective pollinators. To contribute to this debate, and to obtain a contrast between visitors and pollinators, we studied insect and bird visitors to virgin flowers of Hypoestes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 73 publications
1
35
0
Order By: Relevance
“…, ; Padyšáková et al. ). Even when some pollen is delivered, bees that remove more pollen often deposit a smaller percentage of those pollen grains on subsequent flower visits (Harder and Thomson ).…”
Section: Introductionmentioning
confidence: 99%
“…, ; Padyšáková et al. ). Even when some pollen is delivered, bees that remove more pollen often deposit a smaller percentage of those pollen grains on subsequent flower visits (Harder and Thomson ).…”
Section: Introductionmentioning
confidence: 99%
“…Only B. lamium, H. aristata and P. eminii have flowers of mellitophilous pollination syndrome. In our previous studies (Padyšáková et al, 2013;Bartoš et al, 2015), H. aristata and H. roeparianum were shown to be flowers more commonly visited by A. mellifera, while H. revolutum was visited mainly by M. ogouensis.…”
Section: Short Notementioning
confidence: 80%
“…Moreover African sunbirds are known to be relatively unspecialised in terms of morphological adaptations to nectar feeding [29, 30]. To what extent all links (flower visitations) in our network represent pollination rather than nectar robbing, catching visiting insects or even florivory [44, 45] is under investigation. An increase in cheating in visitation networks may destroy nestedness and enforce modularity by which the structure would slow down the spread of disturbances [17, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Our network is not unique in being small, open and including visitors with very different relative contributions to pollination vs eg. nectar robbing [31, 45]. Not all sunbird species are equally dependent on tree species for nectar or forests for habitat, for example Horak et al [38] found that in Cameroon the orange tufted sunbird preferred open mountain vegetation to montane forest.…”
Section: Discussionmentioning
confidence: 99%